Islamisasi Teori Konsumsi Masyarakat Muslim Modern - A'yun Nadhira; Sabila Rosyida (Islamica: Jurnal Studi Keislaman, 2018)
Materialism and consumerism influence people’s consumption behaviour, considering that the purpose of consumption is not only to fulfil life’s needs but also for mere satisfaction. The purpose of this study is to examine the importance of Islamization of economics, especially the theory of consumption, referring to the theory of Islamization of science of al-Attas and al-Faruqi. The results of this study indicate that the Islamization of economics in consumption theory is very important to liberate society from the secular doctrine of materialism; Islamizing the goods and services concept by limiting it with the term of ḥalālan ṭayyiban; incorporating the element of maṣlaḥah as the main foundation in consumption instead of satisfaction. With the Islamization of economics on consumption theory, it is hoped that it can provide a change and enlightenment, particularly in the consumption behaviour of the Muslim community, and generally for economic development.